Suvannabhumi - TIM REDAKSI (Institute for Southst Asian Studies, 2015)
Vol. 9, No. 1, June 2017 Edisi kali ini memuat beberapa artikel, diantaranya: “Local” vs. “Cosmopolitan” in the Study of Premodern Southeast Asia (hal. 7). Affective-discursive Practices in Southeast Asia: appropriating emotive roles in the case of a Filipina domestic helper in Hongkong who fell to her death while cleaning windows (hal. 53). Things Fall Apart? Thailand’s Post-Colonial Politics (hal. 85). Articulations of Southeast Asian Religious Modernism: Islam in early 20th century Cambodia & Cochinchina (hal. 109). An Overview of Southeast Asian Area Studies in the Philippines (hal. 133). Nation-building in Independent Myanmar: a comparative study of a history textbook and a civic textbook (hal. 149). Social Capital Revitilation of the Sasaq Community in Lombok, Indonesia Through Learning Organization (hal. 173).